Effects of age-based stereotype threat on time-based prospective memory - Tsang, Alex Pak Lik; Chan, Stephen Cheong Yu; Lu, Hui Jing; Wong, Chi Chung (Frontiers in Psychology, 2024)
The present study aimed to investigate the effect of a blatant activation of age-based stereotype threats (ABST) on time-based prospective memory (TBPM) in older adults. A sample of 74 adults from Hong Kong was randomly assigned to one of the two experimental conditions: the stereotyped condition (n = 36) or the neutral condition (n = 38). Participants were asked to read fictitious news reports related to dementia (stereotyped condition) or the importance of English oral skills (neutral condition). After, all participants performed a TBPM task using the Chinese lexical decision task as an ongoing task block. The results indicate a main effect of ABST on TBPM accuracy. Specifically, older adults under a blatant activation of ABST demonstrated lower TBPM accuracy (p < 0.05, ηp 2 = 0.08). Further analyses based on age groups demonstrated that TBPM accuracy was only impaired in older participants (aged 70-80 years) (p < 0.05, ηp 2 = 0.19). The study, for the first time, provides evidence that ABST can disrupt TBPM performance in older adults, especially when cues are blatantly activated.